Reflexiones acerca de la competencia y la colaboración - Viteri Gordillo, Mónica (2019)
Th e present study aims to present some refl ections on the interdisciplinary aspects involved in competition and collaboration, in order to relate the variables of fi eld and arena in the performance of a market, with the purpose of reconstructing the classic market model that has been questioned due to the number of problems it has generated, mainly in the generation of unemployment and unequal distribution of income.  Th e economy currently presents serious contradictions that are refl ected in two fundamental aspects: unemployment and surplus production. Th ese two components of the market economy have not been solved by the dynamics of the world market mechanisms, although, from the theoretical point of view, tends to balance. Th ese are the so-called “market failures”, for which State intervention becomes necessary